Russia’s policy in the Eurasian area amid confrontation with the West - S. S. Zhiltsov (Проблемы постсоветского пространства)
Western sanctions against Moscow have led to a radical change in the Russian foreign policy course. The Western direction of Russia’s diplomacy, which had been promoted since the late 1980s, began to change at the end of the XX and at the beginning of the XXI centuries. Amid the Western pressure, Moscow began to give higher priority to the eastern direction, expanding political and economic contacts with non-Western states. Russia’s main attention was turned to the countries of the Eurasian area, for which the policy of the West also created significant risks. As a result, over the past decades, Moscow’s diplomacy has made a radical turnaround, establishing a new framework of economic relations and creating a solid foundation for the further development of political ties with the Eurasian states. Furthermore, in recent years, the forming of new ties with Eurasian countries has rapidly accelerated, primarily due to the worsening of the relations between Russia and the West. This factor provoked a fundamental revision of Moscow’s foreign policy, which was forced to respond to the confrontational course of the Western states. The article analyzes the main results that Russia has achieved in its relations with the Eurasian countries. The research concludes that the shift of Russian policy towards the Eurasian area has a long-term basis and meets the interests of Moscow.